Play Based Development of Children - Soni, Romila (THE PRIMARY TEACHER, 2006)
Play is the most important activity in children’s lives. Play is not only a source of great pleasure for children but also the basis of all their learning and development. Theoretically there is a widespread acceptance of the idea that play is very important for a child; but at the practical level, play is too often replaced with worksheets and highly structured forms of learning. However, research verifies that play is a vehicle that enhances a child’s total development. Play, with or without material, influences all aspects of development, i.e. social, emotional, physical, motor and intellectual.